Analyzing English Language Learning in Elementary Schools During the COVID-19 Pandemic: Challenges and Insights - ., Roni; ., Sunandar; ., Sam Hermansyah; Nurbaya, St (Maspul Journal of English Studies, 2023)
The Covid-19 pandemic has hit various parts of the world. Indonesia is one of the countries affected by COVID-19. A number of schools have been in Indonesia since COVID-19 implementing distance learning in the learning process. The purpose of writing this journal is to analyze the learning process carried out in elementary schools during the COVID-19 pandemic. This type of article is written using qualitative research using literature studies. Studies literature done in writing the article This covers analysis and also a review of related books, articles, journals, or other relevant sources that are continuous with the title. Elementary on the exposure of this journal it was concluded that in the conditions of the COVID-19 pandemic, it is possible for the community to do activities usually, on moment pandemic of course there are restrictions in activities and activities can done in a manner online, and learning. At a number of school points, online learning has been implemented. On subjects Language English in level School Base can in implemented with utilize media learning to support learning activities. By using learning media, learning English will be more effective, and efficient.